A history of the Hasmonean state: Josephus and beyond - Atkinson, Kenneth (Jewish and Christian texts in contexts and related studies, 2016)
"Kenneth Atkinson tells the exciting story of the nine decades of the Hasmonean rule of Judea (152 - 63 BCE) by going beyond the accounts of the Hasmoneans in Josephus in order to bring together new evidence to reconstruct how the Hasmonean family transformed their kingdom into a state that lasted until the arrival of the Romans. Atkinson reconstructs the relationships between the Hasmonean state and the rulers of the Seleucid and the Ptolemaic Empires, the Itureans, the Nabateans, the Parthians, the Armenians, the Cappadocians, and the Roman Republic. He draws on a variety of previously unused sources, including papyrological documentation, inscriptions, archaeological evidence, numismatics, Dead Sea Scrolls, pseudepigrapha, and textual sources from the Hellenistic to the Byzantine periods. Atkinson also explores how Josephus's political and social situation in Flavian Rome affected his accounts of the Hasmoneans and why any study of the Hasmonean state must go beyond Josephus to gain a full appreciation of this unique historical period that shaped Second Temple Judaism, and created the conditions for the rise of the Herodian dynasty and the emergence of Christianity. No extract of this content is available for preview."--Bloomsbury Publishing